A water footprint assessment of primary citrus production in the Lower Sundays River Valley Citrus Farms, Eastern Cape, South Africa - Munro, Samantha Alanna (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2015)
With the current implementation of the South African National Water Act (NWA) underway, comprehensive tools to assist in the efficient, fair and sustainable management of water resources are needed. Water footprints (WFs) are increasingly being recognised as a meaningful way to represent human appropriation of water resources and provide a framework for assessing the sustainability of water use. The study calculated blue, green and grey WFs for the lower Sundays River Valley (LSRV) citrus sector across dry, humid and long-term average climates for a number of cultivars. The sustainability of both the LSRV and the production process of citrus were examined through the adoption of a number of environmental, social and economic indicators. The study revealed that there was no water scarcity in the area because of an inter-basin transfer and that water pollution levels attributed to citrus production required a more comprehensive indicator than the grey WF. Results showed that navels, despite being the dominant cultivar, had the highest WF and the lowest water productivity and technical efficiency. It also provided lower benefits of income and employment in terms of water use in comparison to other cultivars. Conversely, cultivars such as lemons, which required a greater amount of water and fertiliser, were the most productive cultivar with the lowest blue, green and grey WF. The study demonstrated the complexity of decisions regarding water management and the need to assess accurately the environmental, social and economic implications of strategies to increase efficiency of water. The importance of incorporating local data and verifying WFs was also illustrated. The analysis highlighted that WF assessments could be useful for the South African government and agricultural sectors to assist in future water management decisions and promote increased collaboration between stakeholders. The study found that the adoption of local benchmarks could be useful in aiding the promotion of more efficient water use and could factor in sensitive economic and social attributes. WFs in conjunction with other economic and social indicators could also be used to evaluate the sustainability of current and future allocations pertaining to the implementation of the NWA. It was however noted that this requires vast amounts of accurate data.
Keywords: Water efficiency -- South Africa -- Eastern Cape -- Evaluation; Water consumption -- Environmental aspects -- South Africa -- Eastern Cape; Citrus -- Water requirements -- South Africa -- Eastern Cape